Halogen-free low-smoke flame-retardant material and preparation process thereof

By using a blending technology of composite flame retardant and maleic anhydride graft modified polyethylene and magnesium hydroxide, the inorganic flame retardant has low heat resistance, poor compatibility and reduced mechanical properties in polyolefin materials. Problem, higher flame retardant and heat resistance are achieved.

CN119431938AInactive Publication Date: 2025-02-14CHONGQING SAIYI POLYMER MATERIAL CO LTD

Patent Information

Application Number
CN202411807667.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing inorganic flame retardants have problems such as low heat resistance, poor compatibility and reduced mechanical properties in improving the flame retardant properties of polyolefin materials.

Method used

Using a composite flame retardant, the dispersion of inorganic filler is improved by hydrolysis of thiol silane coupling agent and the formation of thiol-modified aluminum hydroxide, combined with the pre-melting blending of maleic anhydride grafted modified polyethylene and magnesium hydroxide. and compatibility, form a continuous crosslinking network structure.

Benefits of technology

The dispersion and compatibility of inorganic fillers in polymer matrix are improved, and a more continuous cross-linking network structure is formed, which improves the flame retardant and heat resistance of the material, while improving mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431938A_ABST
    Figure CN119431938A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of flame-retardant materials, in particular to a halogen-free low-smoke flame-retardant material and a preparation process thereof. The halogen-free low-smoke flame-retardant material is prepared from the following raw materials: an ethylene-vinyl acetate copolymer, linear low-density polyethylene, maleic anhydride grafted modified polyethylene, a composite flame retardant, magnesium hydroxide, a synergistic flame retardant, an interface modifier and the like. The composite flame retardant is prepared from a sulfydryl-containing silane coupling agent, aluminum hydroxide and vinyl acetate. A composite flame retardant is prepared from a mercapto silane coupling agent, aluminum hydroxide and vinyl acetate as raw materials, the composite flame retardant is introduced into a material system, the dispersity and compatibility of inorganic filler in a polymer group are improved, a more continuous cross-linked network structure is formed, high-speed dry mixing, melt mixing and extrusion molding by a double-shaft eccentric rotor extruder are adopted, and the flame-retardant composite material is prepared. The processability of the material and the quality of a final product are improved, and the flame retardant property of the material is improved through the synergistic effect of the synergistic flame retardant.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of flame retardant materials, and in particular to a halogen-free low-smoke flame retardant material and a preparation process thereof. Background Art

[0002] Traditional cable sheathing materials (such as PVC) will produce a large amount of harmful gases and thick smoke when burned, while polyolefins have become the preferred main material for environmentally friendly cable sheathing materials because of their high temperature resistance, high flame retardancy, low smoke and halogen-free characteristics. When polyolefin materials burn, they decompose water and carbon dioxide, and do not produce obvious smoke and toxic gases. Polyolefins mainly include PE, PP, EVA, ethylene propylene rubber, etc., which have excellent electrical insulation and mechanical properties. However, polyolefin materials themselves are flammable, so flame retardants are usually used, among which inorganic flame retardants are the most commonly used. These inorganic flame retardants form a cross-linked network structure to limit the movement of molecular chains, thereby improving the thermal decomposition temperature and solid-like behavior of the material to achieve a flame retardant effect.

[0003] Despite this, inorganic flame retardants still have shortcomings in improving the flame retardant properties of polyolefin materials. For example, the heat resistance of inorganic flame retardants is low, which will affect the stability of the material at high temperatures. Secondly, the compatibility between inorganic fillers and polyolefin matrix is ​​poor, resulting in uneven dispersion of fillers in the matrix, affecting the overall performance of the material. In addition, when the amount of inorganic fillers added is high, the mechanical properties of the material will be reduced. Although cross-linking technology is currently used to improve it, such as peroxide chemical cross-linking, which belongs to a free radical initiation system, it will lead to discontinuity of the cross-linking network, and the compatibility problem between the filler and the matrix still exists, resulting in low flame retardant properties of flame retardant materials. Summary of the invention

[0004] In view of the deficiencies in the prior art, the object of the present invention is to provide a halogen-free low-smoke flame retardant material and a preparation process thereof.

[0005] A halogen-free low-smoke flame retardant material, composed of the following raw materials in parts by weight: 60-90 parts of ethylene-vinyl acetate copolymer (EVA), 10-15 parts of linear low-density polyethylene (LLDPE), 10-15 parts of maleic anhydride grafted modified polyethylene (MAH-g-PE), 60-100 parts of composite flame retardant, 50-80 parts of magnesium hydroxide, 10-30 parts of synergistic flame retardant, 1-1.5 parts of interface modifier, 0.5-1 part of antioxidant and 3-5 parts of silicone;

[0006] The preparation method of the composite flame retardant is as follows: (1) adding ethanol, dilute hydrochloric acid or dilute sulfuric acid, and deionized water into a reactor, stirring and mixing evenly, slowly dropping a mercapto-containing silane coupling agent, heating to 80-90° C. for hydrolysis reaction for 8-12 hours, cooling to room temperature, and drying the reaction precipitate;

[0007] (2) adding the reaction precipitate into dichloromethane or tetrahydrofuran to dissolve it, adding aluminum hydroxide, stirring and dispersing it evenly, and continuing the reaction for 2-4 hours to obtain a mixture;

[0008] (3) mixing the mixture with vinyl acetate, adding a photocatalyst, and irradiating the mixture under ultraviolet light of 365-405 nm wavelength for 15-30 min to obtain a composite flame retardant;

[0009] The synergistic flame retardant is basic magnesium sulfate whisker (MHSH) and / or organic montmorillonite (OMMT).

[0010] Furthermore, the mercapto-containing silane coupling agent is γ-mercaptopropyltriethoxysilane or γ-mercaptopropyltrimethoxysilane, and the photocatalyst is one of benzoin dimethyl ether, benzoin ethyl ether, bisbenzoylphenylphosphine oxide and 2,4-dihydroxybenzophenone.

[0011] Furthermore, the mass ratio of the mercapto-containing silane coupling agent to aluminum hydroxide is 1:5-10, the mass ratio of the mercapto-containing silane coupling agent to vinyl acetate is 1:1-3, and the amount of the photocatalyst is 0.5-1% of the total mass of the mercapto-containing silane coupling agent, aluminum hydroxide and vinyl acetate.

[0012] Specifically, the vinyl acetate content of the ethylene-vinyl acetate copolymer is 27.0 wt% and the melt index is 3.0 g / 10 min; the melt index of the linear low-density polyethylene is 2.0 g / 10 min (210° C., 2.16 kg); and the MAH group content of the maleic anhydride grafted modified polyethylene is 0.5-0.8 wt% and the melt index is 0.9-1.6 g / 10 min.

[0013] Specifically, the average particle size of the aluminum hydroxide is 2.0-2.4 μm, and the average particle size of the magnesium hydroxide is 1.5 μm.

[0014] Specifically, the basic magnesium sulfate whiskers have an average diameter of 0.9-1.1 μm and a length of 10-40 μm; the organic montmorillonite has an average particle size of 16-20 μm and is modified with dihydrogenated tallow dimethyl ammonium chloride.

[0015] Specifically, the antioxidant is distearyl thiodipropionate (DSTDP), and the polysiloxane content of the silicone is 55%.

[0016] Furthermore, the interface modifier is vinyl tris (2-methoxyethoxy) silane.

[0017] A preparation process of a halogen-free low-smoke flame retardant material comprises the following steps:

[0018] (1) Ethylene-vinyl acetate copolymer and linear low-density polyethylene are uniformly mixed, a composite flame retardant and a synergistic flame retardant are added, and dry-mixed for 10-15 minutes using a high-speed mixer, and then an interface modifier, an antioxidant and silicone are pre-mixed to form a premix;

[0019] (2) Premixing maleic anhydride grafted modified polyethylene and magnesium hydroxide, adding them to an internal mixer and melt mixing them for 5-10 minutes, continuing to add the premix, melt blending them at 140° C. for 20-30 minutes to form a flame retardant material, extruding them through a twin-shaft eccentric rotor extruder, and pressing them into sheets through a flat vulcanizer at 180° C., and cutting them into standard strips to obtain a halogen-free and low-smoke flame retardant material.

[0020] Specifically, the specific parameters of the twin-shaft eccentric rotor extruder are: zone 1 temperature 80°C, zone 2 temperature 140°C, zone 3 temperature 160°C, zone 4 temperature 160°C, die head temperature 160°C, rotation speed 40rpm, and feeding speed 30kg / h.

[0021] The beneficial effects achieved by the present invention are as follows: 1. The present invention obtains a composite flame retardant through the hydrolysis of a mercaptosilane coupling agent, mercapto-modified aluminum hydroxide, and mercapto-ene click chemical reaction, and introduces the composite flame retardant into a halogen-free and low-smoke flame retardant material system to improve the dispersibility and compatibility of inorganic fillers in a polymer group, forming a more continuous cross-linked network structure, and adopts high-speed mixer dry mixing, internal mixer melt mixing, and twin-shaft eccentric rotor extruder extrusion molding to ensure uniform dispersion and good molding of the material. The combined use of the internal mixer and the twin-shaft eccentric rotor extruder improves the processing performance of the material and the quality of the final product. The synergistic effect of the synergistic flame retardant further improves the flame retardant performance of the material and enhances the heat resistance.

[0022] 2. The present invention promotes the hydrolysis of the mercaptosilane coupling agent by acidic catalysis to form active silanol groups, and after redissolving, adds aluminum hydroxide and stirs to disperse, so that the silanol groups react with the hydroxyl groups on the surface of the aluminum hydroxide to form mercapto-modified aluminum hydroxide, which is then mixed with vinyl acetate, and a photocatalyst is added to carry out a mercapto-ene click chemistry reaction to obtain mercapto-modified aluminum hydroxide grafted with vinyl acetate, thereby improving the dispersibility and compatibility of the inorganic filler in the polymer matrix.

[0023] 3. The present invention pre-melt-blended maleic anhydride grafted modified polyethylene (MAH-g-PE) and magnesium hydroxide, so that the polar groups on the MAH-g-PE and the hydroxyl groups on the surface of the inorganic filler (magnesium hydroxide) form hydrogen bonds or other chemical bonds, and interact to form physical or chemical cross-linking points, thereby improving the interfacial bonding force and compatibility between the inorganic filler and the polymer matrix, helping to reduce the agglomeration of the filler and making the filler more evenly distributed in the matrix. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The present invention is a schematic flow chart of the preparation process of the halogen-free low-smoke flame retardant material. DETAILED DESCRIPTION

[0025] The technical solution of the present invention is further described below in conjunction with specific implementation methods.

[0026] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art.

[0028] In the following examples, the vinyl acetate content of ethylene-vinyl acetate copolymer is 27.0wt% and the melt index is 3.0g / 10min; the melt index of linear low density polyethylene is 2.0g / 10min (210°C, 2.16kg); the MAH group content of maleic anhydride grafted modified polyethylene is 0.5-0.8wt% and the melt index is 0.9-1.6g / 10min; the average particle size of aluminum hydroxide is 2.0-2.4μm, and the average particle size of magnesium hydroxide is 1.5μm; the average diameter of basic magnesium sulfate whiskers is 0.9-1.1μm and the length is 10-40μm; the average particle size of organic montmorillonite is 16-20μm, and it is modified in advance with dihydrogenated tallow dimethyl ammonium chloride; the antioxidant is distearyl thiodipropionate, the polysiloxane content of silicone is 55%, and the interface modifier is vinyl tris(2-methoxyethoxy)silane.

[0029] The specific parameters of the twin-shaft eccentric rotor extruder for extrusion molding are: temperature of zone 1 80℃, temperature of zone 2 140℃, temperature of zone 3 160℃, temperature of zone 4 160℃, head temperature 160℃, rotation speed 40rpm, and feeding speed 30kg / h.

[0030] Embodiment 1: A halogen-free low-smoke flame retardant material is composed of the following raw materials in parts by weight: 75 parts of ethylene-vinyl acetate copolymer, 12 parts of linear low-density polyethylene, 12 parts of maleic anhydride grafted modified polyethylene, 80 parts of composite flame retardant, 65 parts of magnesium hydroxide, 20 parts of synergistic flame retardant (basic magnesium sulfate whisker), 1.2 parts of interface modifier, 0.7 parts of antioxidant and 4 parts of silicone;

[0031] The preparation method of the composite flame retardant is as follows: (1) adding ethanol, dilute hydrochloric acid and deionized water into a reactor, stirring and mixing evenly, slowly dropping a mercapto-containing silane coupling agent (γ-mercaptopropyltriethoxysilane), heating to 85° C. for hydrolysis reaction for 10 h, cooling to room temperature, and drying the reaction precipitate;

[0032] (2) adding the reaction precipitate into dichloromethane or tetrahydrofuran to dissolve it, adding aluminum hydroxide, stirring and dispersing it evenly for 3 hours, so that the silanol groups react with the hydroxyl groups on the surface of the aluminum hydroxide to form thiol-modified aluminum hydroxide, and obtaining a mixture;

[0033] (3) mixing the mixture with vinyl acetate, adding a photocatalyst (benzoin dimethyl ether), and irradiating the mixture under ultraviolet light of 405 nm wavelength for 20 min to carry out a thiol-ene click chemical reaction to obtain aluminum hydroxide modified with thiol and grafted with vinyl acetate, a composite flame retardant;

[0034] The mass ratio of the mercapto-containing silane coupling agent to aluminum hydroxide is 1:8, the mass ratio of the mercapto-containing silane coupling agent to vinyl acetate is 1:2, and the amount of the photocatalyst is 0.8% of the total mass of the mercapto-containing silane coupling agent, aluminum hydroxide and vinyl acetate.

[0035] A preparation process of a halogen-free low-smoke flame retardant material, such as Figure 1 As shown, the following steps are included:

[0036] (1) Ethylene-vinyl acetate copolymer and linear low-density polyethylene are uniformly mixed, a composite flame retardant and a synergistic flame retardant are added, dry-mixed for 12 minutes using a high-speed mixer, and then an interface modifier, an antioxidant and silicone are pre-mixed to form a premix;

[0037] (2) Maleic anhydride grafted modified polyethylene and magnesium hydroxide are premixed, added to an internal mixer and melt mixed for 8 minutes, and the premix is ​​continuously added, and melt blended at 140° C. for 25 minutes to form a flame retardant material, which is extruded by a twin-shaft eccentric rotor extruder, and sheeted by a flat vulcanizer at 180° C., and cut into standard strips to obtain a halogen-free and low-smoke flame retardant material.

[0038] Example 2: A halogen-free low-smoke flame retardant material, composed of the following raw materials in parts by weight: 65 parts of ethylene-vinyl acetate copolymer, 15 parts of linear low-density polyethylene, 15 parts of maleic anhydride grafted modified polyethylene, 60 parts of composite flame retardant, 50 parts of magnesium hydroxide, 25 parts of synergistic flame retardant (organic montmorillonite), 1 part of interface modifier, 0.7 parts of antioxidant and 4 parts of silicone;

[0039] The preparation method of the composite flame retardant is as follows: (1) adding ethanol, dilute sulfuric acid and deionized water into a reactor, stirring and mixing evenly, slowly dropping a mercapto-containing silane coupling agent (γ-mercaptopropyltrimethoxysilane), heating to 80° C. for hydrolysis reaction for 12 h, cooling to room temperature, and drying the reaction precipitate;

[0040] (2) adding the reaction precipitate into dichloromethane or tetrahydrofuran to dissolve it, adding aluminum hydroxide, stirring and dispersing it evenly for 2 hours, so that the silanol groups react with the hydroxyl groups on the surface of the aluminum hydroxide to form thiol-modified aluminum hydroxide, and obtaining a mixture;

[0041] (3) mixing the mixture with vinyl acetate, adding a photocatalyst (benzoin ethyl ether), and irradiating the mixture under ultraviolet light of 405 nm wavelength for 25 min to carry out a thiol-ene click chemistry reaction to obtain aluminum hydroxide modified with thiol and grafted with vinyl acetate, a composite flame retardant;

[0042] The mass ratio of the mercapto-containing silane coupling agent to aluminum hydroxide is 1:10, the mass ratio of the mercapto-containing silane coupling agent to vinyl acetate is 1:3, and the amount of the photocatalyst is 0.8% of the total mass of the mercapto-containing silane coupling agent, aluminum hydroxide and vinyl acetate.

[0043] A preparation process of a halogen-free low-smoke flame retardant material, such as Figure 1 As shown, the following steps are included:

[0044] (1) Ethylene-vinyl acetate copolymer and linear low-density polyethylene are uniformly mixed, a composite flame retardant and a synergistic flame retardant are added, and dry-mixed for 15 minutes using a high-speed mixer, and then an interface modifier, an antioxidant and silicone are pre-mixed to form a premix;

[0045] (2) Maleic anhydride grafted modified polyethylene and magnesium hydroxide are premixed, added to an internal mixer and melt mixed for 5 minutes, and the premix is ​​continuously added, and melt blended at 140° C. for 20 minutes to form a flame retardant material, which is extruded by a twin-shaft eccentric rotor extruder, and sheeted by a flat vulcanizer at 180° C., and cut into standard strips to obtain a halogen-free and low-smoke flame retardant material.

[0046] Embodiment 3: A halogen-free low-smoke flame retardant material, composed of the following raw materials in parts by weight: 85 parts of ethylene-vinyl acetate copolymer, 10 parts of linear low-density polyethylene, 10 parts of maleic anhydride grafted modified polyethylene, 90 parts of composite flame retardant, 55 parts of magnesium hydroxide, 10 parts of synergistic flame retardant (basic magnesium sulfate whisker), 1.5 parts of interface modifier, 0.7 parts of antioxidant and 4 parts of silicone;

[0047] The preparation method of the composite flame retardant is as follows: (1) adding ethanol, dilute hydrochloric acid and deionized water into a reactor, stirring and mixing evenly, slowly dropping a mercapto-containing silane coupling agent (γ-mercaptopropyltriethoxysilane), heating to 90° C. for a hydrolysis reaction for 9 h, cooling to room temperature, and drying the reaction precipitate;

[0048] (2) adding the reaction precipitate to dichloromethane or tetrahydrofuran to dissolve it, adding aluminum hydroxide, stirring and dispersing it evenly for 2.5 hours, so that the silanol groups react with the hydroxyl groups on the surface of the aluminum hydroxide to form thiol-modified aluminum hydroxide, and obtaining a mixture;

[0049] (3) mixing the mixture with vinyl acetate, adding a photocatalyst (benzoin dimethyl ether), and irradiating the mixture under ultraviolet light of 405 nm wavelength for 30 min to carry out a thiol-ene click chemical reaction to obtain aluminum hydroxide modified with thiol and grafted with vinyl acetate, a composite flame retardant;

[0050] The mass ratio of the mercapto-containing silane coupling agent to aluminum hydroxide is 1:5, the mass ratio of the mercapto-containing silane coupling agent to vinyl acetate is 1:1, and the amount of the photocatalyst is 0.5% of the total mass of the mercapto-containing silane coupling agent, aluminum hydroxide and vinyl acetate.

[0051] A preparation process of a halogen-free low-smoke flame retardant material, such as Figure 1 As shown, the following steps are included:

[0052] (1) Ethylene-vinyl acetate copolymer and linear low-density polyethylene are uniformly mixed, a composite flame retardant and a synergistic flame retardant are added, dry-mixed for 12 minutes using a high-speed mixer, and then an interface modifier, an antioxidant and silicone are pre-mixed to form a premix;

[0053] (2) Premixing maleic anhydride grafted modified polyethylene and magnesium hydroxide, adding them into an internal mixer and melt mixing them for 10 minutes, continuing to add the premixed materials, and melt blending them at 140° C. for 30 minutes to form a flame retardant material, extruding them through a twin-shaft eccentric rotor extruder, and pressing them into sheets through a flat vulcanizer at 180° C., and cutting them into standard strips to obtain a halogen-free and low-smoke flame retardant material.

[0054] Comparative Example 1: Compared with Example 1, in this comparative example, the composite flame retardant is replaced with aluminum hydroxide, and a halogen-free and low-smoke flame retardant material is prepared.

[0055] Comparative Example 2: Compared with Example 1, in this comparative example, the synergistic flame retardant is replaced with aluminum hydroxide, and a halogen-free and low-smoke flame retardant material is prepared.

[0056] Performance test: relevant performance tests were performed on the halogen-free low-smoke flame retardant materials of Examples 1-3 and Comparative Examples 1-2;

[0057] 1. Flame retardant performance test: According to the UL 94 vertical combustion test standard (GB / T 2408-2008 "Vertical method for determining the combustion performance of plastics"), the flame retardant grade of the material (V-0, V-1, V-2) is evaluated.

[0058] 2. Mechanical properties test: The tensile strength and elongation at break of the material are tested in accordance with GB / T 1040.1-2018 "Determination of tensile properties of plastics Part 1: General principles"; the flexural strength and flexural modulus of the material are tested in accordance with GB / T 9341-2008 "Determination of flexural properties of plastics".

[0059] 3. Thermal performance test: The glass transition temperature and melting temperature of the material are tested in accordance with GB / T 19466.3-2009 "Plastics Differential Scanning Calorimetry (DSC) Part 3: Determination of Melting and Crystallization Temperature and Thermal Enthalpy".

[0060] 4. Environmental resistance test: Test the material's UV resistance in accordance with GB / T 16422.2-2014 "Plastics Laboratory Light Source Exposure Test Methods Part 2: Xenon Arc Lamp".

[0061] The test results are shown in Table 1 and Table 2.

[0062] Table 1 Flame retardant and mechanical properties test results of halogen-free low-smoke flame retardant materials

[0063]

[0064] Table 2 Test results of thermal properties and environmental resistance of halogen-free low-smoke flame retardant materials

[0065]

[0066] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A halogen-free low-smoke flame retardant material, characterized in that: The invention is composed of the following raw materials in parts by weight: 60-90 parts of ethylene-vinyl acetate copolymer, 10-15 parts of linear low-density polyethylene, 10-15 parts of maleic anhydride grafted modified polyethylene, 60-100 parts of composite flame retardant, 50-80 parts of magnesium hydroxide, 10-30 parts of synergistic flame retardant, 1-1.5 parts of interface modifier, 0.5-1 parts of antioxidant and 3-5 parts of silicone; The preparation method of the composite flame retardant is as follows: (1) adding ethanol, dilute hydrochloric acid or dilute sulfuric acid, and deionized water into a reactor, stirring and mixing uniformly, slowly adding a mercapto-containing silane coupling agent dropwise, heating to 80-90° C. for hydrolysis reaction for 8-12 hours, cooling to room temperature, and drying the reaction precipitate; (2) adding the reaction precipitate into dichloromethane or tetrahydrofuran to dissolve, adding aluminum hydroxide, stirring and dispersing uniformly, and continuing the reaction for 2-4 hours to obtain a mixture; (3) mixing the mixture with vinyl acetate, adding a photocatalyst, and irradiating under ultraviolet light with a wavelength of 365-405 nm for 15-30 minutes to obtain a composite flame retardant; The synergistic flame retardant is basic magnesium sulfate whisker and / or organic montmorillonite.

2. The halogen-free low-smoke flame retardant material according to claim 1, characterized in that: The mercapto-containing silane coupling agent is gamma-mercaptopropyl triethoxysilane or gamma-mercaptopropyl trimethoxysilane, and the photocatalyst is one of benzoin dimethyl ether, benzoin ethyl ether, bisbenzoylphenyl phosphine oxide and 2,4-dihydroxybenzophenone.

3. The halogen-free low-smoke flame retardant material according to claim 1, characterized in that: The mass ratio of the mercapto-containing silane coupling agent to aluminum hydroxide is 1:5-10, the mass ratio of the mercapto-containing silane coupling agent to vinyl acetate is 1:1-3, and the amount of the photocatalyst is 0.5-1% of the total mass of the mercapto-containing silane coupling agent, aluminum hydroxide and vinyl acetate.

4. The preparation process of a halogen-free low-smoke flame retardant material according to claim 1, characterized in that: By weight, the vinyl acetate content of the ethylene-vinyl acetate copolymer is 27.0wt% and the melt index is 3.0g / 10min; the melt index of the linear low-density polyethylene is 2.0g / 10min; the MAH group content of the maleic anhydride grafted modified polyethylene is 0.5-0.8wt% and the melt index is 0.9-1.6g / 10min.

5. The halogen-free low-smoke flame retardant material according to claim 1, characterized in that: The average particle size of the aluminum hydroxide is 2.0-2.4 μm, and the average particle size of the magnesium hydroxide is 1.5 μm.

6. The halogen-free low-smoke flame retardant material according to claim 1, characterized in that: The basic magnesium sulfate whisker has an average diameter of 0.9-1.1 μm and a length of 10-40 μm; the organic montmorillonite has an average particle size of 16-20 μm and is modified with dihydrogenated tallow dimethyl ammonium chloride.

7. The halogen-free low-smoke flame retardant material according to claim 1, characterized in that: The antioxidant is distearyl thiodipropionate, and the polysiloxane content of silicone is 55%.

8. The halogen-free low-smoke flame retardant material according to claim 1, characterized in that: The interface modifier is vinyl tris (2-methoxyethoxy) silane.

9. The process for preparing a halogen-free low-smoke flame retardant material according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: (1) uniformly mixing ethylene-vinyl acetate copolymer and linear low-density polyethylene, adding a composite flame retardant and a synergistic flame retardant, and dry-mixing them for 10-15 minutes using a high-speed mixer, and then pre-mixing an interface modifier, an antioxidant and silicone to form a premix; (2) pre-mixing maleic anhydride grafted modified polyethylene and magnesium hydroxide, adding them to an internal mixer for melt mixing for 5-10 minutes, continuing to add the premix, and melt blending them at 140°C for 20-30 minutes to form a flame retardant material, extruding it through a double-shaft eccentric rotor extruder, and pressing it into sheets through a flat vulcanizer at 180°C, and cutting them into standard strips to obtain a halogen-free and low-smoke flame retardant material.

10. The process for preparing a halogen-free low-smoke flame retardant material according to claim 9, characterized in that: The specific parameters of the twin-shaft eccentric rotor extruder are: zone 1 temperature 80°C, zone 2 temperature 140°C, zone 3 temperature 160°C, zone 4 temperature 160°C, die head temperature 160°C, rotation speed 40rpm, and feeding speed 30kg / h.

Citation Information

Patent Citations

  • Ultra-low smoke density halogen-free flame-retardant cable material and preparation method thereof

    CN109593266A

  • Chemically modified white graphene based on mercapto-ene click addition and preparation method thereof

    CN109850885A

  • UV crosslinked low-smoke halogen-free flame-retardant polyolefin cable material and preparation method thereof

    CN111548545A

  • Polyolefin composition as well as preparation method and application thereof

    CN115368669A

  • Ultraviolet crosslinking wear-resistant short-circuit-resistant halogen-free flame-retardant polyolefin material capable of resisting temperature of 125 DEG C and preparation method thereof

    CN115612199A

Cited By

  • Flame-retardant high-temperature-resistant modified plastic and processing method thereof

    CN121108616A

  • Low-smoke halogen-free insulating material as well as preparation method and application thereof

    CN122145918A